Do the patients referred to the emergency department really deserve an urgent medical intervention? (Annals of Medical Research, 2021)
Aim: In this study, it was aimed to evaluate the urgency of the patients considering their referral complaints indicated by 112 ambulance service crew and their anamnesis obtained in the emergency department (ED) as well. The evaluation was performed according to the World Health Organization (WHO) - 32 - Emergency Parameters (EP).Material and Methods:This retrospective study was carried out examining the data of all patients brought to our hospital’s ED by the 112-ambulance service between the dates January 05, 2017 and October 31, 2017. Qualitative and quantitative evaluations are based on the WHO-32-EP.Results: Findings: The age of the emergency patients was found to be statistically higher than that of non-emergency patients (p= 0.024). It was observed that 171 patients evaluated according to their referral complaints were not in an urgent condition and that 109 patients evaluated according to their anamnesis obtained in the ED were not in an urgent condition as well. When the relationship between the complaints of the patients at the moment of the referral to the ED by 112 ambulance crew, and their anamnesis obtained in the ED, it was found that 24.6% (n = 99) of these patients were not in an urgent condition. Most of the complaints reported by 112 ambulance crew were not found in the WHO-32-EP (n=170).Conclusion: Awareness-raising training may be useful for 112 ambulance service crews that provide on-site emergency medical care so that they can make accurate decisions about diagnosis and perform accurate initial intervention as well. Keywords: Emergency Referral; Emergency Medicine; WHO; 112 Emergency Service.
Keywords: Emergency Referral; Emergency Medicine; WHO; 112 Emergency Service.